Tempo, memória e direito: um estudo jurídico, político e filosófico sobre o patrimônio cultural imaterial - Oliveira, David Barbosa de (2011)
This research titled Time, memory and law: legal, political and philosophical study of the intangible cultural heritage is a study about the intangible cultural heritage and its relationship with memory, democracy and the weather. For time, we try to initially demonstrate that society and the memory are socially constructed since the memory is not a natural given, but a choice, an ideologically determined selection. We discuss the origin of cultural heritage and its evolution to its assimilation by national states. Established, throughout the text, what is the relationship between law, culture and memory, as well as the cultural heritage is a cultural fundamental right. Understood that cultural heritage is the legal protection over a selected memory ideologically expounded the development of intangible cultural protection to the Constituent 1987, as the result of these discussions, namely the effective protection in the constitution of 1988 still approached the relationship between democracy and pluralism and the infra protection for the intangible cultural heritage. Finally, we analyze the influence of time on cultural heritage. Thus, we expose the philosophical development over time of classical thought to Hegel. Then we use Heidegger's thought and his concept of time originating in explaining how the weather affects on the protection of intangible cultural heritage, specifically how the law can manage the experience of doing / expressing the intangible cultural asset. Thus, we believe that this dissertation contributes to discussions about intangible cultural heritage in its relation with time, memory, and legal pluralism, and offers new theoretical instrument in the defense and management of cultural property.